Young people's contraception and sexual health: Report of a local needs assessment in Staveley, North Derbyshire. Issue 1 (1st January 2001) - Smith, Amanda
Abstract : This project assessed the contraception and sexual health needs of people aged under 25 years in the small town of Staveley, UK, and sought to determine how the community family planning service could best meet these needs. One hundred and seventeen young people and 17 local professionals took part. The preferred ideal was found to be a holistic youth service based in an accessible, non-clinic setting. Clinic-based services should be more user-friendly, and various ways to achieve this were suggested. Both clients and professionals need greater awareness of all local services.